The creation of social value in the participatory design of housing services - Giiulia Vignati; Gianluca Pozzi; Silvia Meazza (Techne)
The approach to housing that redefines the home as a service transcends the issue of housing as merely private, bringing it back to a trajectory of collective public interest. The paper reflects on initiatives, whose common element is the investment in intangible aspects for community involvement, activating processes and experiments for the development of collaborative spaces and services that extend the scope of intervention to the neighbourhood, generating mechanisms and dynamics of social impact. The processes and experiments described are examples of how, to make such actions feasible, the public sector synergises with the private sector through welfare models requiring innovative management skills that invest and work on the community with an integrated approach for social cohesion.